Identification of future activities of enterprises regarding the growth of innovativeness = Identyfikacja przyszłych działań przedsiębiorstw w zakresie wzrostu innowacyjności - Skawińska, Eulalia; Zalewski, Romuald I. (Zielona Góra: Faculty of Economics and Management Press)
The article contains the results of a survey conducted among 259 companies in Greater Poland from 1000 of those entities which had received the questionnaire using a random-proportional selection. This paper?s structure consists of three parts theoretical one and two which characterize empirical work.
Keywords: innowacyjność; rynki przyszłościowe; przewaga konkurencyjna przedsiębiorstw; innovativeness; future markets; competitive advantage of companies